Art 38 Basel : Galerie Michael Haas, Galerie Haas & Fuchs Berlin. - Basel (Basel Berlin : Art Basel Galerie Haas & Fuchs Berlin Galerie Michael Haas Berlin, 2007)
Adami, Valerio ; Arp, Hans (Jean) ; Bess, Forrest ; Braque, Georges ; Chia, Sandro ; Cucchi, Enzo ; Ensor, James ; Fautrier, Jean ; Gertsch, Franz ; Jahns, Rudolf ; Kirchner, Ernst Ludwig ; Klapheck, Konrad ; Leger, Fernand ; Lindner, Richard ; Magritte, René ; Masson, Andre ; Nolde, Emil ; Picabia, Francis ; Rouault, Georges ; Soutter, Louis ; Stella, Frank ; Tàpies, Antoni ; Venet, Bernar ; Warhol, Andy
Publikation anlässlich der Ausstellung 'Art 38 Basel' in Basel, 13.06.2007 - 17.06.2007
boek